The obesity paradox in patients with atrial fibrillation: an insight from the Gulf SAFE registry. (25th November 2020) - Li, Y.G; Bai, J; Domek, M; Alsheikh-Ali, A; Almahmeed, W; Shehab, A; Sulaiman, K; Asaad, N; Liu, S.W; Zubaid, M; Lip, G.Y.H
Abstract: Background: The prognostic role of obesity among patients with atrial fibrillation (AF) is unclear. Methods: A total of 1804 patients with AF had body mass index (BMI) measures from the Gulf survey of atrial fibrillation events (Gulf SAFE) registry were implied. A multivariable model was established to investigate the role of obesity on clinical outcomes, including stroke or systemic embolism, bleeding, admission for heart failure (HF) or AF, all-cause mortality and composite event. Results: 559 (31.0%) patients were identified as obesity (BMI over 30kg/m 2 ). In multivariable analyses, obesity was associated with reduced risks of stroke/systematic embolism (hazard ratio [HR] 0.40, 95% confidence interval [CI] 0.18–0.89), major or clinical relevant bleeding (HR 0.44, 95% CI 0.26–0.74), HF admission (HR 0.61, 95% CI 0.41–0.90) and composite outcome (HR 0.65, 95% CI 0.50–0.84). Higher BMI was associated with lower risks of stroke/systemic embolism, bleeding, admission for HF, all-cause mortality, and composite outcomes as were demonstrated by accumulated incidence of events and restricted cubic splines. Conclusion: Among patients with AF, higher BMI was associated with a more favorable prognosis. Funding Acknowledgement: Type of funding source: None